Identification and Characterization of Two Novel Mutations (Q421K and R123P) in Congenital Factor XII Deficiency - Kanaji, Taisuke; Kanaji, Sachiko; Osaki, Koichi; Kuroiwa, Mika; Sakaguchi, Masao; Mihara, Katsuyoshi; Niho, Yoshiyuki; Okamura, Takashi (Thrombosis and Haemostasis, 2001)
The factor XII genes of two unrelated factor XII-deficient Japanese families were screened, and two novel mutations were identified. A heterozygous mutation (Q421K) was identified in the gene of a cross-reacting material (CRM)-negative patient with reduced FXII activity (entitled Case 1). No mutations were discovered in the other allele. Case 2 was a CRM-negative patient with severe FXII deficiency. In this case, a homozygous mutation (R123P) was discerned. Expression studies in Chinese Hamster Ovary (CHO) cells demonstrated accumulation of mutant Q421K factor XII in the cell, and insufficient secretion, while the R123P mutant showed lower levels of accumulation than wild-type, and no evidence of secretion in culture supernatant. In the presence of proteasome inhibitor, all types of FXII (wild-type, Q421K, R123P) accumulated in the cells. Protease protection experiments using the microsomal fraction of these cell lines demonstrated that while 20% wild-type FXII (total wild-type:100%) and 10% R123P mutant (total R123P-type: 40%) were resistant to treatment with trypsin, 50% Q421K-type FXII (total Q421K-type:130%) remained resistant to digestion. From these results, we conclude that Q421K is less susceptible to proteasome degradation than wild-type, but is unable to exit the ER efficiently, resulting in insufficient secretion phenotype. In contrast, R123P is susceptible to proteasome degradation and is not secreted.
Keywords: FXII deficiency; mutation; proteasome